(untitled) (Journal of Atomic and Molecular Sciences, 2010)
Two-dimensional modified Peierls-Nabarro dislocation equation concerning the discreteness of crystals is reduced to one-dimensional equation to determined the core structure of partial dislocation in Ag. The generalized stacking fault energy along the Burgers vectors of partial dislocation is a skewed sinusoidal force law, which is related to the intrinsic stacking fault energy and the unstable stacking fault energy. A trial solution appropriate for arbitrary dislocation angle is presented within the variational method. The results show that the half core width increases as the increase of dislocation angle. Moreover, the core width decreases with the increase of the unstable stacking fault energy and the intrinsic stacking fault energy. Peierls stress for 60^° partial dislocation is in agreement with the experimental results.